Analysis of Financial Statements Based on ISAK 335 at the “Bala Keselamatan” Foundation - North Sulawesi - Walangare, Isahbella; Evinita, Lenny; Miran, Michael (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
The Bala Keselamatan Foundation in the North Sulawesi region is a non-profit entity. This research aims to analyze the financial report format of ISAK 335 for non-profit entities at the Salvation Army Foundation in the North Sulawesi region and to prepare financial reports based on ISAK 335. The research method used is descriptive qualitative. The data sources in this research come from primary and secondary data. The data collection techniques used include observation, interviews, and documentation. The research results show that the financial reporting at the Salvation Army Foundation does not yet use ISAK No. 335. They prepare financial reports based on the standards set by the Salvation Army Headquarters; therefore, the author restructured the financial report format of the Salvation Army based on ISAK 335. Furthermore, according to ISAK 335, there are 5 components, namely the statement of financial position, statement of comprehensive income, statement of changes in net assets, cash flow statement, and notes to the financial statements.